Fully integrated current-mode quadrature sinusoidal oscillator circuit - Kumngern, Montree; Chanwutitum, Jirasak; Dejhan, Kobchai (My University, 2011)
This paper presents a new mixed-mode quadrature oscillator using one current controlled current conveyor (CCCII), one CCCII with controlled current gain and two grounded capacitors. The oscillation condition and the oscillation frequency can be controlled orthogonally and electronically by the bias currents of the CCCIIs. The circuit provides two quadrature voltage outputs and four quadrature current outputs and then can be classified as a mixed-mode oscillator. Simulation results that confirm the theoretical predictions are also given. © 2011 IEEE.
Keywords: current controlled current conveyor (CCCII); current-mode circuit; quadrature oscillator